Avaliação da relação entre composição corporal e biodisponibilidade de uma formulação de diclofenaco sódico - Capistrano Júnior, Valden Luis Matos (2017)
Introduction: The increase of chronic-degenerative diseases has a great relation with the body composition, both in the obesity process and in clinical cases of sarcopenia in which both, according to the literature, can cause changes in the pharmacokinetics of the drugs. Objective: To evaluate the relationship between body composition and bioavailability of diclofenac sodium formulation in healthy volunteers. Methods: This was a cross-sectional study, consisting of twenty-four healthy subjects (age range: 18-50 years) who received 50 mg of oral sodium diclofenaco. Hematological, biochemical and physical methods (bioelectric impedance method) were obtained before study admission. Pharmacokinetics parameters were evaluated by high performance liquid chromatography coupled to mass spectrometry. The relationships between pharmacokinetics and body composition were evaluated with Pearson correlations. Student's t-test was used for continuous variables and was established at p <0.05. Results: There was a significant inverse correlation between an area under a concentration time curve of 0 to 24h (water), intracellular water (r = -0.4917, p = 0.0147) = -0.4406, p = 0. 0312), extracellular water (r = -0.4964, p = 0.0136) and basal metabolic rate (r = -0.5033, p = 0.0122); (R = -0.4908, p = 0.0149), intracellular water (r = -0.4401, p = 0.0314), between the area under the concentration time curve from zero to infinity (ASC0-), Extracellular water (r = -0.4946, p = 0.0140) and basal metabolic rate (r = -0.5023, p = 0.0124); (R = -0.7290, p <0.0001), intracellular water (r = -0.6750, p = 0.0003), extracellular water (r = -0.7519, p <0.0001) (R = -0.7505, p <0.0001). Conclusion: The low values of ASC0-t (h) and ASC0- are associated with higher values of lean body mass, intracellular water, extracellular water and basal metabolic rate. Adequacy of the dose of diclofenac sodium based on these can avoid prescription errors, improve prognosis and reduce side effects.